1994
DOI: 10.1002/chin.199445169
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Reaction of Benzylidenebenzocyclanones with Dithiocarbamic Acid and Thiourea.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…6 Later, we have reported on stereochemical analysis of reactions with dithiocarbamic acid of (E)-2-benzylidenecyclohexanones 8,9 and some (E)-2-benzylidene-1-benzocylanones. 10 Reactions of the investigated compounds led to formation of cyclic 8,9 or open chain 10 adducts. Stereochemistry of the formed adducts were found to be determined by both the structure of the α,β-unsaturated carbonyls and the reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…6 Later, we have reported on stereochemical analysis of reactions with dithiocarbamic acid of (E)-2-benzylidenecyclohexanones 8,9 and some (E)-2-benzylidene-1-benzocylanones. 10 Reactions of the investigated compounds led to formation of cyclic 8,9 or open chain 10 adducts. Stereochemistry of the formed adducts were found to be determined by both the structure of the α,β-unsaturated carbonyls and the reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the reaction results in formation either open-chain or cyclic adducts depending on the substitution pattern of the aromatic rings of the chalcones [6]. Later, we have reported on stereochemical analysis of reactions with dithiocarbamic acid of (E)-2-benzylidenecyclohexanones [8,9] and some (E)-2-benzylidene-1-benzocylanones [10]. Reactions of the investigated compounds led to formation of cyclic [8,9] or open chain [10] adducts.…”
mentioning
confidence: 97%
“…Later, we have reported on stereochemical analysis of reactions with dithiocarbamic acid of (E)-2-benzylidenecyclohexanones [8,9] and some (E)-2-benzylidene-1-benzocylanones [10]. Reactions of the investigated compounds led to formation of cyclic [8,9] or open chain [10] adducts. Stereochemistry of the formed adducts were found to be determined by both the structure of the α,b-unsaturated carbonyls and the reaction conditions.…”
mentioning
confidence: 99%
“…However an alternative direction is also mentioned in the literature for the interaction of α,β-unsaturated ketones with thioureas leading to the formation of a dihydrothiazine ring. Nucleophilic addition of mercapto group with subsequent cyclization is characteristic of cyclic unsaturated ketones [4,5], and also on using N-arylthioureas in the reaction [6,7]. N N Me O Me O N NH Ar O R O N N O Me O Me O N N Me Ar O Me 4 5 R = H, Ar…”
mentioning
confidence: 99%